2018
DOI: 10.1584/jpestics.d18-004
|View full text |Cite
|
Sign up to set email alerts
|

Status and use of pesticides in forage crops in India

Abstract: The Indian livestock population is huge. Most (99%) of the livestock owners still follow traditional animal husbandry practices and graze their livestock, especially small ruminants, on natural pastures where no pesticides are used. In order to feed the everincreasing livestock population, efforts are being made to increase quality fodder productivity from limited land resources. In such situations, pesticides play an important role by minimizing the loss of green fodder due to disease and pest attack. In coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Damage caused by pests can reach up to 80-100% in the case of agricultural treatment [61][62][63][64] for effective plant management [65][66][67][68][69][70]. The results of this study showed that we detected a highly significant difference between the genotypes in relation to the percentage of germination (Table 1).…”
Section: Influence Of Pesticides On Germination and Anthesismentioning
confidence: 58%
“…Damage caused by pests can reach up to 80-100% in the case of agricultural treatment [61][62][63][64] for effective plant management [65][66][67][68][69][70]. The results of this study showed that we detected a highly significant difference between the genotypes in relation to the percentage of germination (Table 1).…”
Section: Influence Of Pesticides On Germination and Anthesismentioning
confidence: 58%
“…Although pastures take up around two-third of global agricultural land 31 , only a small fraction of grazing area is managed and cultivated in many parts of the world. For example, >90% of permanent pastures in China, India, Argentina, Mexico, and Australia are natural and unmanaged 31,46,47 . In managed pastures, pesticides are normally used during sowing.…”
Section: Resultsmentioning
confidence: 99%
“…are reported to cause damage to berseem during their different growth stages (Shah et al 2010). The use of pesticides in forage crops has certain constraints, such as low feasibility due to high cost/ benefit ratio, residue accumulation in the food chain through milk and milk products, and even direct toxicity to livestock (Koli and Bhardwaj 2018). Due to the lipophilic nature of pesticides, they easily get accumulated in milk and other fat-rich substances finding its way through animalderived products (John et al 2001).…”
Section: Introductionmentioning
confidence: 99%